Access to treatment for those with alcohol, crack or other drug dependency problems - a case study in the municipality of Rio de Janeiro, Brazil - José Mendes Ribeiro (Ciência & Saúde Coletiva, 2016)
Changes in psychiatric policies has meant more emphasis on the protection of the individual's rights, tougher regulations and disincentives regarding involuntary patient admissions, and the creation of a community network to support individuals needing help. The differing socioeconomic status of those requiring treatment coupled with guidelines issued by the Health Ministry has meant that more support and care is now being directed towards individuals and families. The rise in public awareness of the problems in these areas has aided in the changes that have taken place. Due to a lack of community public services, this has led to the proliferation of different types of services all with differing standards of care and has fueled the public debate surrounding involuntary patient admissions. Our analysis in relation to treatment for those with alcohol, crack and other drugs problems in the municipality of Rio de Janeiro, states that there are gaps related to access for all-day public services and a lack of psychiatrists in multi-disciplinary teams. There are many new and untried serviced offered by the private sector, religious bodies and public shelters which have arisen in the wake of the rise in people that need help. We took note of the development and progress of these new projects as well as the policy recommendations from the Government.